Introduction to the acoustics of the Colombian Andean bandola (2013)
In this article, we present the Colombian Andean bandit in the context of musical acoustics. We mention some of the physical phenomena involved in the generation of sound and the relationship with the construction of the instrument. Taking advantage of the similarity with the guitar - in origin and construction - we use a simplified mechanical model for the study of coupled resonances, which fed on the results obtained by simulations with the finite element method.